Rhizosphere microbiome selection by Epichloë endophytes of Festuca arundinacea - Roberts, Elizabeth Lewis; Ferraro, Aileen (Plant and Soil, 2015)
Aims: Loline alkaloids produced by Epichloë spp. are known to deter feeding by insect herbivores while also serving as a significant carbon source for certain epiphytic bacteria on tall fescue leaves. In this study we examined the role of loline alkaloids in attracting certain bacteria to the rhizosphere of tall fescue plants that harbor loline producing fungal endophytes. Methods: Population studies were used to compare the fitness of known loline catabolizing strains to other rhizosphere bacteria. Pyrosequencing of 16S rRNA fragments compared the composition of bacterial communities inhabiting the endophyte infected tall fescue (Festuca arundinacea) rhizosphere to those of endophyte free fescue plants. Results: Rhizosphere population studies demonstrated that loline catabolizing strains Burkholderia ambifaria 7R and Pseudomonas aureofaciens outcompete and suppress the growth of non-loline catabolizing strains. Pyrosequencing of 16S rRNA fragments showed greater percentages of certain plant growth promoting bacteria in rhizosperes seeded with B. ambifaria 7R than non-inoculated soils. Rhizospheres of endophyte infected plants showed higher species richness (Shannon diversity index = 4.03) over endophyte free rhizospheres (Shannon diversity index = 3.08) and a greater percentage of Firmicutes. Conclusions: The differences in microbial community composition between endophyte-infected and endophyte-free rhizospheres suggest that the presence of fungal endophytes influences microbial community structure. Loline alkaloid production may be one proxy by which the fungal endophyte shapes microbial communities, as evidenced by increased fitness of loline catabolizing bacteria in the tall fescue rhizosphere. © 2015, Springer International Publishing Switzerland.
Keywords: Bacteria (microorganisms); Burkholderia ambifaria; Endophyte; Epichloë spp; Festuca arundinacea; Firmicutes; Hexapoda; Loline alkaloids; Pseudomonas chlororaphis; Tall fescue; alkaloid; antifeedant; bacterium; community structure; dept.bio; diversity index; endophyte; fitness; fungus; grass; insect; microbial community; microorganism; rhizosphere; species richness